2018
DOI: 10.1080/16549716.2019.1625594
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with past year physical and sexual intimate partner violence against women in Zimbabwe: results from a national cluster-based cross-sectional survey

Abstract: Background: Intimate partner violence (IPV) against women continues to be a public health burden globally. Objectives: To assess prevalence and factors associated with women's experiences of past 12 months physical/sexual IPV Methods: A two-stage cluster-based national cross-sectional survey in which women were randomly selected for participation was conducted among 5295 women aged 15-49 years. IPV in the last 12 months was assessed using the WHO interviewer-administered questionnaire for measuring violence ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
13
17
1
1
Order By: Relevance
“…In concert with other studies, our study highlights that police officers may even side with the aggressor or hold a patriarchal view, considering abuse as a personal and family issue rather than a societal and legal problem [14]. This may enhance the gender inequitable norms and encourage such practices in the society [32]. This also illustrates that the responses of IPV in pregnancy by agencies are shaped by existing structural and socio-cultural norms [23].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In concert with other studies, our study highlights that police officers may even side with the aggressor or hold a patriarchal view, considering abuse as a personal and family issue rather than a societal and legal problem [14]. This may enhance the gender inequitable norms and encourage such practices in the society [32]. This also illustrates that the responses of IPV in pregnancy by agencies are shaped by existing structural and socio-cultural norms [23].…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with the Connell’s theory of gender and power, social constructs, including the sexual division of labour, power and social norms, conflict/violence in marriage is taken for granted, and women are expected to be tolerant and sacrificial [30,31], enforcing the tendency to preserve women’s subordination. Other studies also confirm the gender inequitable norms and practices linked to IPV [32,33,34]. Men’s cultural and historical authority further strengthens their general sense of power over their partners, and if this power is threatened, permission to resort to violence [35].…”
Section: Discussionmentioning
confidence: 81%
“…Academic qualification is said to be a source of knowledge for the individual that is utilized in many ways. Previous studies support these findings (Aol´ain, O'Rourke, & Swaine, 2012a;Shamu, Shamu, & Machisa, 2018). Previous studies on intimate violence (Birkley & Eckhardt, 2015;Stith, Smith, Penn, Ward, & Tritt, 2004) point to the fact that most violence in HIV infections is perpetrated in discordant infections but in this study, it was found that even in concordant infections perpetration of intimate partner violence was prevalent as participants argued with their partners as to who was the cause of the infection.…”
Section: Discussionsupporting
confidence: 72%
“…Given the higher odds of males experiencing violence overall, primary violence prevention interventions, such as Stepping Stones 27,28 , Family Matters 3 29 and SASA! 30 , are needed to tackle harmful cultural norms that perpetuate violence among boys and decrease tolerance of violence overall 31,32 . These programs should target both boys and girls, men and women, as parents play a key role in the reduction of violence against children and teens 16 .…”
Section: Discussionmentioning
confidence: 99%